A conceptual paper to develop a strategic performance scorecard for private secondary schools - Bisschoff, Christo (Journal of Economic Development, Environment and People, 2026)
Private secondary schools in South Africa face several challenges in measuring their performance. These include the absence of a precise delineation of performance objectives, inadequate monitoring and evaluation systems, restricted use of data-driven decision-making procedures, and a lack of coherence between the school’s overarching strategic objectives and daily operational activities. This study uses a conceptual approach to develop a tailor-made performance management scorecard for private secondary schools in South Africa by reviewing 220 published studies. The four key antecedents comprise 1) the student’s perspective, 2) academic excellence, 3) learning and growth, and 4) resources. Each antecedent also comprises sub-constructs from which the measuring criteria can be structured. This scorecard is helpful to school managers, school boards, and researchers because it can be used to measure the performance of private secondary schools as a first step toward improving performance management.